1992
DOI: 10.1016/0885-3924(92)90061-l
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil: Clinical use as postoperative analgesic—Epidural/intrathecal route

Abstract: Although morphine and fentanyl remain the predominant epidural opioids, sufentanil offers some unique advantages. Because of its greater lipophilicity and mu-receptor binding capacity, sufentanil has a faster onset of action and longer duration than epidural fentanyl. Compared with morphine, sufentanil has been associated with a lower incidence of side effects, particularly delayed respiratory depression. The effective doses and adverse effects profile of epidural sufentanil are relatively well understood. Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…[5] Its delayed onset of analgesic effect[67] and late onset respiratory depression limits its widespread routine use. [8] In contrast, sufentanil is a lipid soluble drug with high receptor affinity and intense analgesia of rapid onset,[9] its only limitation being short duration of analgesia,[10] which necessitates continuous infusion. [11]…”
Section: Introductionmentioning
confidence: 99%
“…[5] Its delayed onset of analgesic effect[67] and late onset respiratory depression limits its widespread routine use. [8] In contrast, sufentanil is a lipid soluble drug with high receptor affinity and intense analgesia of rapid onset,[9] its only limitation being short duration of analgesia,[10] which necessitates continuous infusion. [11]…”
Section: Introductionmentioning
confidence: 99%
“…9 Epidural sufentanil, when compared with morphine, has been associated with a lower incidence of delayed respiratory depression. 10 However, the incidence of PONV has remained high in patients administered epidural sufentanil. 11 -13 Previous studies reported that small doses of the opioid antagonist naloxone administered i.v.…”
mentioning
confidence: 99%
“…Glass reported relative lipid solubilities for opioids: morphine, 1; hydromorphone, 1.4; meperidine, 28; methadone, 82; fentanyl, 580; and sufentanil, 1280. (1) The hydrophilicity (or lipophilicity) of a drug is a significant determinant of duration of action (and onset of action) when the drug is delivered intrathecally. Morphine, hydromorphone, and meperidine are all poorly lipid soluble.…”
Section: Discussionmentioning
confidence: 99%